2004
DOI: 10.1042/bj20031637
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide 1-phosphate enhances calcium entry through voltage-operated calcium channels by a protein kinase C-dependent mechanism in GH4C1 rat pituitary cells

Abstract: Sphingomyelin derivatives modulate a multitude of cellular processes, including the regulation of [Ca2+]i (the intracellular free calcium concentration). Previous studies have shown that these metabolites often inhibit calcium entry through VOCCs (voltage-operated calcium channels). In the present study, we show that, in pituitary GH4C1 cells, C1P (C2-ceramide 1-phosphate) enhances calcium entry in a dose-dependent manner. The phospholipase C inhibitor U73122 attenuated the response. C1P invoked a small, but s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…C1P, an anionic lipid, might therefore interact directly with this domain in a fashion analogous to that by which phosphatidylserine interacts with the C2 domain of PKC. Alternatively, C1P could also indirectly activate cPLA 2 ␣ since exogenous C1P has been reported to induce calcium mobilization (Tornquist et al, 2004). We have recently discovered that C1P is indeed a direct activator of cPLA 2 ␣ that interacts with its C2/CaLB domain (Subramanian et al, 2005).…”
Section: C1p and S1p In Inflammatory Responsesmentioning
confidence: 99%
“…C1P, an anionic lipid, might therefore interact directly with this domain in a fashion analogous to that by which phosphatidylserine interacts with the C2 domain of PKC. Alternatively, C1P could also indirectly activate cPLA 2 ␣ since exogenous C1P has been reported to induce calcium mobilization (Tornquist et al, 2004). We have recently discovered that C1P is indeed a direct activator of cPLA 2 ␣ that interacts with its C2/CaLB domain (Subramanian et al, 2005).…”
Section: C1p and S1p In Inflammatory Responsesmentioning
confidence: 99%
“…This led to proposal of the cytosolic phospholipase A 2a (cPLA 2a ) as the first molecular target of C1P (7). Other studies have suggested a role of ceramide kinase/ C1P in mast cell degranulation (8), regulation of acidic sphingomyelinase and control of apoptosis in bone marrowderived macrophages (9), calcium mobilization in GH4C1 pituitary and Jurkat T-cells (10,11), and dopamine release in PC12 cells (12). A role for C1P in fibroblast proliferation was reported a decade ago (13,14).…”
mentioning
confidence: 99%
“…Nevertheless, many laboratories, including ours, have tried to elucidate ceramide kinase signaling pathways by adding exogenous C1P to cells in culture. Although reports are still not numerous, there is already complexity attributable to variability in the choice of the acyl chain length of the C1P used, or in the choice of the organic solvent used, such as DMSO (10,11), methanol/chloroform (16), or ethanol (or methanol)/dodecane (5)(6)(7)14); others have prepared fine dispersions of C1P by sonication in aqueous medium (13,15). The ethanol (or methanol)/ dodecane mixture, in particular, used at 98:2, was first reported 10 years ago (14) and proposed to be useful to elucidate the biological functions and mechanisms of action of C1P.…”
mentioning
confidence: 99%
“…*represent statistical significant difference between groups. In the control and in rLiD1 treated group the dP/dt max and dP/dt min were, respectively (in mmHg/sec) 1536,5±55,7 and 1392,8±37,6 (p = 0.0508); and -819,1±29,0 and -710,3±23,0 (p = 0,010) 5±33,0±11,0±7,7±40,0±39,6±33,6 Discussion Sphingomyelin is the main substrate of phospholipase D. Sphingomyelin products such as sphingosine and ceramide modulate potently cell activity by the activation of a G protein, triggering a cascade of events leading changes in intracellular Ca ++ concentration which affects the activity of enzymes involved in the regulation of Ca ++ and modulating intracellular Ca ++ levels (Tornquist et al, 2004). Ceramide can be phosphorylated by ceramide kinase originating ceramide-1-phosphate.…”
Section: Resultsmentioning
confidence: 99%